ANALISIS BUKU AJAR BAHASA ARAB KELAS VIII MADRASAH TSANAWIYAH TERBITAN KARYA PUTRA KERTONATAN: ANALISIS BUKU AJAR BAHASA ARAB KELAS VIII MADRASAH TSANAWIYAH TERBITAN KARYA PUTRA KERTONATAN - Putri Intan Rahayu Lestari (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2023)
Textbooks are an important component in learning, therefore they must meet the criteria for textbooks that are suitable for use according to applicable regulations. Content analysis is a method for studying and analyzing something systemically and objectively to the messages that appear. The content of textbooks is a source of material in the learning process. Therefore, textbooks must comply with the applicable curriculum. Related to the analysis of Arabic textbooks, several studies have been found that examine the feasibility of Arabic textbooks. extbooks must meet the criteria for textbooks that are suitable for use which have been determined (BSNP). And the teaching material in it is a quality teaching material. The purpose of this study was to find out the class Arabic textbooks seven Published by Putra Kertonan. Does the textbook meet the standards (BSNP) and has met the quality of textbooks based on aspects of selection, gradation, presentation, and repetition.